FULL DAY SCHOOL AND HALF DAY SCHOOL ON STUDENT LEARNING ACHIEVEMENT AT JATI AGUNG AL QADIRY HIGH SCHOOL AND YPM 4 BOHAR SIDOARJO: COMPARATIVE STUDY - Fathul Fauzi; Abdullah Abdullah (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to analyze the differences in learning achievement between students who follow the Full Day School and Half Day School system at the Junior High School level. The research method used is a comparative quantitative study with an Independent Samples T-Test approach. The research sample consisted of 60 VIII grade students, 30 students each from Full Day school and 30 students from Half Day school. Learning achievement data were obtained through report cards with a scale of 10-100. Normality (Shapiro-Wilk) and homogeneity (Levene's Test) assumption tests showed that the data were normally distributed and had homogeneous variances, so they were eligible for the t-test. The analysis showed a significant difference between the two groups (t(58) = 2.272; p = 0.0268 < 0.05), with the average score of Full Day students (M = 76.57; SD = 7.17) higher than Half Day students (M = 71.97; SD = 8.46). The mean difference of 4.6 points indicates a moderate effect based on the calculation of Cohen's d = 0.59. This finding indicates that the Full Day School system has the potential to improve learning achievement through increased learning time, intensive interaction with teachers, and wider enrichment opportunities.